1965
DOI: 10.2307/1994230
|View full text |Cite
|
Sign up to set email alerts
|

On the Fourth Coefficient of Bounded Univalent Functions

Abstract: This class has often been studied in the equivalent form of normalized univalent functions F{z) = fe1_1/(2) = z+ Ï tv\ (2) a, = A, \Fiz)\ib;K We shall study estimates for the coefficient aA in dependence on the first coefficient by .¡For this purpose an inequality of the Grunsky-Nehari type [2], [3] will be used. Such inequalities were first applied by V. Singh [4] in studying the coefficient a4 of bounded univalent functions with real coefficients. The method of Singh, which follows the argument of Charzynski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The Pick function does not give the maximum to |a 3 | and the estimate is much more difficult. Schiffer and Tammi [229] in 1965 found that |a 4 | ≤ p 4 (M) for any f ∈ S M with M > 300. This result was repeated by Tammi [247, page 210] in a weaker form (M > 700) and there it was conjectured that this constant could be decreased until 11.…”
Section: Applications To Extremal Problems Optimal Controlmentioning
confidence: 99%
“…The Pick function does not give the maximum to |a 3 | and the estimate is much more difficult. Schiffer and Tammi [229] in 1965 found that |a 4 | ≤ p 4 (M) for any f ∈ S M with M > 300. This result was repeated by Tammi [247, page 210] in a weaker form (M > 700) and there it was conjectured that this constant could be decreased until 11.…”
Section: Applications To Extremal Problems Optimal Controlmentioning
confidence: 99%
“…Hence the above inequality is also sharp for functions in 5(0 when 1< t ^ δ π . Finally we remark that Schiffer and Tammi [6] have shown that if suffices to take δ 4^ 34/19. We now use Theorems A, B, and C to prove Theorem 1.…”
mentioning
confidence: 90%
“…If f(z) = z + Σ x n=2 a n z\ z E K, is in l/(O,then Schiffer and Tammi [6] showed that \a 4 \^Λ 4 (t), for ί ^ 33 1/3. If in addition / has real coefficients, then Singh [8] proved that \a 4 \^A 4 (t) for t ^ 11.…”
mentioning
confidence: 99%
“…The Pick function does not give the maximum to |a 3 | and the estimate is much more difficult. M. Schiffer and O. Tammi [15] in 1965 found that |a 4 | ≤ p 4 (M ) for any f ∈ S M with M > 300. This result was repeated by O. Tammi [18, page 210] in a weaker form (M > 700) and there it was conjectured that this constant could be decreased until 11.…”
mentioning
confidence: 99%